Chronic joint symptoms in adults: A population-based study - Morais, Silvia Helena de Oliveira; Segheto, Wellington; Silva, Danielle Cristina Guimarães da; Coelho, France Araújo; Reis, Vanessa Guimarães; Ferreira, Fabrícia Geralda; Martinho, Karina Oliveira; Rocha, Anna Lígia Cabral da; Pessoa, Milene Cristine; Longo, Giana Zarbato (Revista da Associação Médica Brasileira, 2017)
To analyze factors associated with chronic joint symptoms (CJS) in adults. A population-based, cross-sectional study was performed with a sample of 1,217 adults aged between 20 and 59 years, in the city of Viçosa, in 2014. The sampling process was performed by conglomerates and sample was selected using a two-stage cluster-sampling scheme. First, 30 of the 99 census tracts of Viçosa were randomly selected using a random sampling scheme, without replacement. Household questionnaires were applied to obtain CJS data, sociodemographic conditions, behavioral factors and health status. Multivariable analysis was conducted using Poisson regression, adjusted for the sampling design effect, using the svy commands in Stata software. Prevalence of CJS totaled 31.27%, significantly higher in women (18.45). Age ranges 40-49 (PR 1.50; 95CI 1.16-1.92) and 50-59 years (PR 1.55; 95CI 1.07-2.25); overweight (PR 1.60; 95CI 1.28-2.00); obesity (PR 1.60; 95CI 1.11-2.29); and those who self-reported performing heavy work (PR 1.27; 95CI 1.09-1.48) showed higher prevalences of CJS. Women and individuals who were older, overweight and performing heavy work had a higher risk of CJS in this adult population residing in Viçosa, MG, Brazil.

Analisar os fatores associados aos sintomas articulares crônicos (SAC) em adultos. Trata-se de um estudo transversal, de base populacional, com 1.217 adultos, na faixa etária de 20 a 59 anos, na cidade de Viçosa, MG, 2014. A amostragem foi realizada por conglomerados em duplo estágio, sendo as unidades de primeiro estágio os setores censitários, e, em seguida, os domicílios. Foram sorteados 30 setores dentre os 99 de Viçosa, por meio de amostragem casual simples, sem reposição. A coleta de dados foi composta por aplicação de questionário contendo questões relativas a variáveis de SAC, sociodemográficas, comportamentais e de saúde. Para verificar as associações, apresentaram-se proporções, razões de prevalência e seus respectivos intervalos de confiança de 95%. A análise múltipla foi realizada por meio da regressão de Poisson, utilizando o conjunto de comandos svy do software Stata, o qual considera o efeito da expansão da amostra na análise dos dados. A prevalência estimada de SAC foi de 31,27%, maior nas mulheres (18,45%). Estiveram associadas ao SAC as mulheres (RP 1,49; IC95% 1,23-1,81); as idades de 40 e 49 (RP 1,50; IC95% 1,16-1,92) e 50 e 59 anos (RP 1,55; IC95% 1,07-2,25); o sobrepeso (RP 1,60; IC95% 1,28-2,00); a obesidade (RP 1,60; IC95% 1,11-2,29); e aqueles que autorreferiram realização de trabalho pesado (RP 1,27; IC95% 1,09-1,48). O sexo feminino, a faixa etária de 40 a 59 anos, o sobrepeso, a obesidade e a realização de trabalho pesado foram fatores de risco para SAC em adultos de Viçosa, MG.
Keywords: Health surveys; Rheumatic diseases; Joints; Adults